Multi-frequency acoustic method and equipment for cement bond log of wells based on one-sided excitation and reception of elastic waves from the top of the well - N. K. Andreev; A. S. Malatsion (Известия высших учебных заведений: Проблемы энергетики)
A brief overview of the method and the description of the device to control the cementation of well casing based on one-sided excitation and reception of elastic waves from the top of the well is given. The mathematical model of propagation of elastic waves in the system of a well casing and its cement ring containing defective and defect-free areas is considered. The influence of the reflection waves from the boundaries of the two solid mediums, and the frequency dependence of the attenuation coefficient of elastic waves and location of defective areas along the pipeline of a well are taken into account. The method is sufficiently rapid, does not require the lowering of the measurement instrument into the well body and is therefore less costly in comparison with other methods. A method is proposed to use in combination with other geophysical methods of well logging.